Casa Cogollo in Vicenza knowned as “Andrea Palladio’s house” - Bartelmus, Bartłomiej (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The author concentrates on the silhouette of a famous Italian Renaissance architect Andrea Palladio. His work is presented on the basis of the history of “Casa Cogollo” – a building situated in Vicenza.